Methods for Inhibiting Virus Replication (2013)
The present invention provides methods for treating a subject having, or at risk of having, a viral infection. The methods include, but are not limited to, the use of 4-(dipropylsulfamoyl)benzoic acid, an inhibitor of CDC25B phosphatase, an inhibitor of ICAM-1, an inhibitor of CamK2B, or a combination thereof.